Impacts of ownership concentration and liquidity on stock momentum profitability in Malaysia - Tan, Yeng May; Cheng, Fan Fah; Hassan, Taufiq (Asian Academy of Management (AAM) and Penerbit Universiti Sains Malaysia, 2018)
This paper explores the effects of two characteristics ubiquitously relevant to the emerging markets in Asia concerning on momentum profitability. By utilising the data of 776 stocks listed on Bursa Malaysia from the period of 2006 to 2014, the study examined how ownership concentration affected momentum profitability. The results of this study revealed that the higher the ownership concentration, the more profitable the momentum investment strategy. It is posited that concentrated ownership led to lower corporate transparency and higher information asymmetry. Hence, resulting to stronger momentum effect. The study also investigated the impacts of liquidity on the profitability of momentum trading strategy. Our results show that price momentum strategies worked better among higher liquidity (smaller spread) stocks.